Aspirin Resistance and Newer Combatants against It (Faridpur Medical College Journal, 2014)
Aspirin is the widely used cheap antiplatelet agent globally. Since marketing it was unbeaten for use in coronary diseases and ischemic stroke patients. Unfortunately for the last two decades the term ''Aspirin resistance'' (AR) has been evolved due to it's failure to protect the aspirin users against major cardiovascular events. Although the PlA1/A2 polymorphism in the GPIIIa platelet receptor along with other factors have been identified as responsible for this resistance, the term has not yet been defined. There is no consensus about ideal platelet function test. So it is more appropriate to say "treatment failure" to aspirin therapy rather using the term AR. Although Clopidogrel is being used alone or in combination with aspirin to overcome AR,platelet receptor (p2y12) inhibitors both Prasugrel and Ticagrelor are more potent than Clopidogrel in Acute Coronary Syndrome (ACS). Worldwide Prasugrel and Ticagrelor have been included in different guidelines to use in ACS DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20394 Faridpur Med. Coll. J. 2013;8(2): 92-95